Activos existentes que presenta el distrito de Tambogrande, región Piura para el desarrollo sostenible del turismo rural comunitario. - Montalván Avalo, Milagro del Socorro (2018)
The present final report of thesis entitled: Existing Assets in the district of Tambogrande - Piura Region for the sustainable development of rural community tourism. As evidenced by the presence of the assets such as natural, cultural, financial and human resources that are part of the virtuous circle that affect the sustainable development of rural community tourism. _x000D_ Natural assets are evidenced in the natural resources such as: The coppers of San Francisco and The Tree lived that help strengthen the development of the rural community tourism based on different aspects such as is its availability for use, the conservation status of the species in which they are today, the variety, the originality that they possess, the accessibility of access to each of them and found both resources and operation for the tourist use. _x000D_ Likewise, The cultural classified assets so much tangible as intangibles. Having to the cultural tangible assets to: As the real estate like The Museum He Marries of the Culture Tambogrande, The Tambo Touristic, machinery like the Petroglyph three spears, The devils painted, facilities as Tambogrande's tourist viewing-point and infrastructure as The tourist oval the peasant, since they are cultural resources of category cultural manifestations and of technical, scientific and artistic contemporary accomplishments, bearing in mind in each of the resources his historical value, the characteristics that the same ones possess and also the hierarchy that they acquire due to the conditions that they find nowadays. _x000D_ In addition the cultural intangible assets are expressed in the gastronomy as the principal local dishes of the district that are: the kid, the ceviche of mackerel, the tortillas with cheese between others, the traditional medicine like the shamanism and the traditional party realized in Tambogrande's district like San Andrés's employer party realized in November of every year and the party of the captive gentleman that given October; they are taken in account as important elements for the sustainable development of the Tourism. _x000D_ As for The financial assets, they are shaped by the traditional activities that Tambogrande's District presents executed by the whole population since it are the Agriculture and the Apiculture. These activities cooperate mutually this way to the sustainable development of the Rural Community Tourism taking as a base his sustenance, tradition, cultural particularities, execution supported in the time and availability of his performers to be taken advantage touristically bearing in mind the exchange of different goods of the capital as the goods and services. _x000D_ Finally another important variable they are the human assets, who are shaped and involved in general by the whole population of the district. Having in it counts the predisposition on the part of Tambogrande's Community expressed in his favorable attitudes and the practice of the fundamental values opposite to the tourists; as well as also the most important the disposition of each one of the settlers to form a part of new developments of Rural Community Tourism and a wide knowledge on the Tambogrande's most representative cultural practices. _x000D_ The used methodology was the Ethnographic method, the Analytical - synthetic method, and the used technologies were direct observation - participant, the interview, the survey and the photographic record.